Predicted Increase in Gold Price Every Year with Impact on Economic Factors - Muhajir Isnin; Ira Zulfa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to develop a predictive model to predict the trend of the emas price over time and to investigate how this affects important economic variables. As a popular commodity that is regarded as a safe refuge for investments, changes in the price of emas can have a significant impact on a number of economic indicators, such as inflation, consumer spending, and investment decisions. Compiling historical data on emas prices, macroeconomic variables, and other related topics is a component of research methodology. Regression analysis and ARIMA modeling are two methods of deret waktu analysis that can be used to create an andal model of problems. The model's predictive accuracy is then determined by using appropriate statistical metrics. This study's findings provide new and important information about the factors influencing changes in the price of emas and how they affect the economy as a whole. The model that is being used can be used by investors, financial institutions, and policymakers to predict gold price movements and make informed decisions to mitigate risks and capitalize on opportunities. The implications of this research extend all the way to the emas market since it increases our understanding of the close relationship between commodity prices and economic dynamics. The knowledge gained can help create more comprehensive investment and economic policies, which will eventually affect the stability of the economy and economic growth.